Influência de diferentes mecanismos de aprendizagem social em uma tarefa de construção: um estudo de evolução cultural cumulativa em laboratório - Saconatto, André Thiago (2017)
Cumulative cultural evolution is a phenomenon that has been studied by a different number of areas in science and it suppose not only transmission, but also the progressive accumulation and modification of behavioral repertoire that would allowed knowledge development that would not be possible to be produced by a single individual alone. A relevant question in those studies is which social learning mechanism(s) is/are accountable for cumulative cultural evolution to occur. The goal of this study was to verify the effect from three different transmission forms – access to the final product, access to the process and instruction – in an experimental task in order to determine if cumulative cultural evolution would occur. In order to reach the goal, a structure construction task using modeling clay and reed were used. The structure was evaluated by putting it over a wooden holder with a hole in the middle of it, and 50-gram weights were thrown above the structure, one by one, until it collapse or a weight touched the table. Two hundred graduates and undergraduates students participated in the research. Participants were distributed into four conditions: at the process condition, participants could see others building their structures; at the final product condition, participants could see the finished structure from the previous participant; at the instruction condition, participants had could read an instruction left from the previous participant. At each condition, there were eight groups, with eight participants in each group, and the next one at the building task followed each participant. At the control condition, eight participants did the building task eight times each (one participant was equivalent to a group from the other conditions). None of the participants had access to the structure evaluation result. The study’s result showed that there were not gradual increase in the number of weights held by the structures as the participants were replaced; and in the groups at the process condition there were a statistical significance in relation to control group, and the number of weights held by the structures this condition were smaller than in the other conditions. One hypotheses is the lack of access to the structure evaluation results by the participants to be a crucial point that contributed to the non-occurrence of the cumulative cultural evolution